Exploring Students’ and Teacher’s Perceptions of Non-Digital Games in Reading - Putri, Amanda Arditya; Sulistyani, Ummi Nur Laila (Journal of English Language and Education, 2026)
Reading motivation is crucial for literacy, yet limited infrastructure in Indonesian rural schools often hinders innovation. Despite the digital learning trend, literature regarding low-cost strategies in resource-constrained settings remains scarce. This study aims to explore student and teacher perceptions of non-digital games, specifically Reading Bingo and Treasure Hunt, to enhance reading engagement at MI Ma’arif Jambu. Employing a descriptive qualitative design with 14 fourth-grade students and one teacher, data were collected via observations, questionnaires, and interviews, then analyzed using the Miles, Huberman, and Saldaña model. Findings revealed that students perceived the games as exciting, with physical movement identified as a key factor in boosting vocabulary comprehension. Furthermore, the teacher perceived these games as feasible ice-breakers creating a lively atmosphere without complex preparation. The study concludes that limited resources are not a barrier to active learning; simple non-digital games offer a high-impact solution for fostering reading motivation.